Indians, Odysseys and Vast, Empty Lands: The Myth of the Frontier in the Canadian Justice System - Furniss, Elizabeth (Anthropologica, 2022)
This article addresses the question of the involvement of anthropologists in political and legal dealings of First Nations with the Canadian government. It is argued that anthropologists would have a greater influence than they do in these matters if their discourse took into account the imaginary constructions of the Canadian population. The analysis focusses on two official texts concerning Aboriginal rights. These texts express imagery and narrative forms that are deeply embedded in Canadian cultural tradition. They reveal myths that influence, though often unconsciously, judgments on the place of Aboriginal populations in the political arena, and that are conceived as common sense. The most recurrent myth which underlines relations of the general population with Aboriginal peoples (a dichotomy which belongs to that myth) is the myth of the frontier whose influence is obvious in the texts analyzed here.